การพัฒนาตัวแบบประเมินประสิทธิผลสำหรับการพัฒนาซอฟต์แวร์แบบสกรัมโดยใช้บาลานซ์สกอร์การ์ด - สุนิสา อติวิทยาภรณ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2012)
This thesis presents a methodology and develops an Effectiveness Evaluation Model for Scrum Software Development using the Balanced Scorecard. The purpose of the model is to ensure that the project meets goals and objectives of project strategies by prioritizing project success factors. The project manager is able to monitor and control the project to agree with the project goal. We use questionnaires to get project goals, strategies perspectives and measure from the Scrum Software project managers. Then we find a relationship between strategies perspectives using Bayesian Network. Then, we map scrum processes onto measurement using Analytical Hierarchy Process (AHP) to help the project manager to find the cause of the problem and solve the problem in correct processes. Finally, we develop an Effectiveness Evaluation tool to monitor and control the project within perspectives of Balance Scorecard.